An Authentic Physics-Based Traction Trebuchet Simulation in Unreal Engine 5 - Broeders, Amy (Wellington Faculty of Engineering Symposium, 2023)
History is commonly perceived as boring and irrelevant to modern youth due to the inaccessible and often dark nature of literature surrounding it. Video games provide a very unique medium to retell stories of epic battles and survival against threats that we rarely worry about today, allowing a broader audience to engage with and learn from our rich history. Traction trebuchets were used for centuries in medieval siege warfare, yet the researcher did not know of their existence prior to starting this project due to the lack of representation in modern media. This project sought to use this modern medium to simulate the machine that would have saved and destroyed many lives with accurate physics and create a fun experience to discover history in a comfortable and accessible setting. In working on this project, it has become clear that the initial vision for this project was ambitious and the game has not lived up to its full potential. However, the physics simulation and accuracy of the trebuchet have been continually prioritised as this will be the most useful artifact to use in future work in this area. The initial work has provided context on some of Unreal Engine’s current physics capabilities, documentation of solutions to bugs created during development that may trip up new learners to Unreal Engine, and a prototype of a traction trebuchet simulation for users to interact with.